How does group counseling increase the self-confidence of adolescent survivors of sexual violence - Yulia Tri Nugrahaini (Research and Social Study Institute, 2021)
The level of self-confidence of survivors of sexual violence needs to get proper attention and treatment. This study aims to determine the effectiveness of group counselling in increasing self-confidence in adolescent sexual violence survivors in Surabaya. The data collection tool used is a self-confidence scale. The subjects of this study were 5 (five) teenagers who had experienced sexual violence and had received psychosocial assistance from the Hotline Surabaya Foundation and the Embun Surabaya Foundation. The research design used is the One Group Pretest-Posttest Design. The analytical method used is the Wilxocon non-parametric data test. The results showed that group therapy was effective in increasing self-confidence in adolescent survivors of sexual violence with a significance of p=0.021 (p<0.05).